Mapping pesticide-induced metabolic alterations in human gut bacteria - Li Chen; Hong Yan; Shanshan Di; Chao Guo; Huan Zhang; Shiqi Zhang; Andrew Gold; Yu Wang; Ming Hu; Dayong Wu; Caroline H. Johnson; Xinquan Wang; et al. (Nature Communications)
Abstract Pesticides can modulate gut microbiota composition, but their specific effects on it remain largely elusive. In our study, we show that pesticides inhibit or promote the growth of various gut microbial species and can be accumulated to prolong their presence in the host. Pesticide exposure also induces significant alterations in gut bacterial metabolism, as reflected by changes in hundreds of metabolites. We generate a pesticide-gut microbiota-metabolite network that not only reveals pesticide-sensitive gut bacteria species but also reports specific metabolic changes in 306 pesticide-gut microbiota pairs. Using an in vivo mouse model, we further demonstrate the interactions of a representative pesticide-gut microbiota pair and verify the inflammation-inducing effects of pesticide exposure on the host, mediated by microbially dysregulated lipid metabolism. Taken together, our findings generate a comprehensive atlas of pesticide-gut microbiota-metabolite interactions atlas and shed light on the molecular mechanisms by which pesticides affect host health via gut microbiota-modulated metabolism.